Use of Smart Contract on Blockchain Technology for Buying and Sale Transactions of Immovable Goods - Efrida Ayni Fikri (Budapest International Research and Critics University, 2022)
Technological sophistication changes the pattern of activity between communities and has an impact on various fields, including the notary field. Prior to the creation of today's technology, buying and selling activities were carried out in the traditional way: the seller met with the buyer, the seller and the buyer agreed to transact at a certain price, made a deed of sale and purchase before a notary, the notary recognized the appearer, affixed a stamp and signature on the deed, and minutes of purchase, which is sewn at the end of the deed. In smart contracts, things like that are no longer applied, because the idea of creating a smart contract is to eliminate the presence of a third party, so that the parties can be directly connected and the process of making a sale and purchase agreement can be done virtually without the intervention of a notary. All the ease of transactions provided by smart contracts do not necessarily eliminate them from shortcomings. The strength of proof on smart contracts is still questionable, because physically smart contracts can only be accessed by the holder.